PERANCANGAN APLIKASI CEK RADIUS OUTLET PT. IJS BERBASIS WEB MENGGUNAKAN METODE HAVERSINE FORMULA - Arron, Rivaltino; Thenata, Angelina Pramana (ZONAsi: Jurnal Sistem Informasi, 2024)
PT. IJS is a company engaged in marketing cafe and restaurant culinary franchise licenses. Opening a new franchise has rules in the form of a radius between locations that cannot be close together. This company still uses a conventional way of checking the location radius, so it takes longer and is less efficient in the checking process. Based on this problem, the researchers built a check radius outlet application for PT. Web-based IJS calculates the shortest distance using the waterfall model and the Haversine Formula method. The designed application is tested using a black box, comparing the system results with actual conditions using an odometer and user acceptance tests. Furthermore, the black box test results were declared successful, and an accuracy value of 94% was obtained with actual conditions. The user acceptance test received a usability level percentage of 89.93% which is very strong from the user's point of view. Keywords: Black Box, Franchise, Metode Haversine Formula, UAT, Waterfall